2017
DOI: 10.3389/fcimb.2017.00154
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Listeria monocytogenes Membrane Vesicles in Inhibition of Autophagy and Cell Death

Abstract: Bacterial membrane vesicle (MV) production has been mainly studied in Gram-negative species. In this study, we show that Listeria monocytogenes, a Gram-positive pathogen that causes the food-borne illness listeriosis, produces MVs both in vitro and in vivo. We found that a major virulence factor, the pore-forming hemolysin listeriolysin O (LLO), is tightly associated with the MVs, where it resides in an oxidized, inactive state. Previous studies have shown that LLO may induce cell death and autophagy. To monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 96 publications
(148 reference statements)
8
40
0
Order By: Relevance
“…EVs carry significant variety of toxins for the parent bacterium, in particular LLO (17,31). We note prior studies that recovered LLO from culture supernatant through protein purification would have included the vesicular fraction and therefore those results are compatible with our findings (44).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…EVs carry significant variety of toxins for the parent bacterium, in particular LLO (17,31). We note prior studies that recovered LLO from culture supernatant through protein purification would have included the vesicular fraction and therefore those results are compatible with our findings (44).…”
Section: Discussionsupporting
confidence: 89%
“…There have been two recent reports of EVs in L. monocytogenes (17,31). In this study, we confirmed these findings, extended the observation that EVs are cytotoxic to murine macrophage-like cells, characterized the secreted EVs using simultaneous metabolite, protein, and lipid extraction (MPLEx) multi-omics approach (32,33), and evidence that EVs are secreted by intracellular bacteria into the cytosol of mammalian cells using electron microscopy and high-resolution fluorescence imaging.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations